2022
DOI: 10.3390/e24081124
|View full text |Cite
|
Sign up to set email alerts
|

Link Prediction in Complex Networks Using Recursive Feature Elimination and Stacking Ensemble Learning

Abstract: Link prediction is an important task in the field of network analysis and modeling, and predicts missing links in current networks and new links in future networks. In order to improve the performance of link prediction, we integrate global, local, and quasi-local topological information of networks. Here, a novel stacking ensemble framework is proposed for link prediction in this paper. Our approach employs random forest-based recursive feature elimination to select relevant structural features associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Studies have demonstrated that XGBoost can achieve higher accuracy and better predictive capabilities in cancer-related tasks. This advantage makes XGBoost a favorable choice for selecting potential biomarkers in cancer research 19,20 .…”
Section: Xgboostmentioning
confidence: 99%
“…Studies have demonstrated that XGBoost can achieve higher accuracy and better predictive capabilities in cancer-related tasks. This advantage makes XGBoost a favorable choice for selecting potential biomarkers in cancer research 19,20 .…”
Section: Xgboostmentioning
confidence: 99%
“…The latter can be achieved by using Recursive Feature Elimination (RFE). RFE is a backward selection method that aims to reduce the number of features while preserving the predictive accuracy of the model ( Wang et al, 2022 ). First, it removes the feature with the lowest relevance to the overall predictive performance.…”
Section: Random Forestmentioning
confidence: 99%